POLITENESS STRATEGIES USED BY AN ENGLISH TEACHER IN THE CLASSROOM AT MTS SWASTA AL-JIHAD MEDAN - Jumita Sari; Rahmad Husein; Syamsul Bahri (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2017)
This study aimed at investigating types of politeness strategies used by an English teacher in the classroom, and to describe the reasons politeness strategies realized by English teacher in the classroom. This study was conducted by applying descriptive qualitative research. The source of the data was an English teacher of class VIII in MTs Swasta Al-Jihad Medan. The researcher used random sampling technique. The instruments of this study were interview and video recording. The data were analyzed using data descriptive. The findings of the result were that: (1) There were three of politeness strategies, namely: Bald on Record (38.1%), Positive Politeness (33.33%), and Negative Politeness (28.57%) and Off Record (0%). (2) Bald on Record was realized because it made close relationship between teacher and students, Positive Politeness was realized because to give respect to the students during teaching learning process, Negative Politeness was realized to maintain closer friend among them, and Off Record never realized by English teacher during teaching learning process. Keywords: Politeness, Politeness Strategies, and Roles of Teacher.